1.Rozwiąż równania:
a) 3(3-x)+2x=8-2(x-1)
b) 4x+5-(3x+6)=2(2+x)-4
c) 4-5(3-x)=-x-(3-2x)
d)x-(7+2x)=2(x-1)+1

2.Rozwiąż równania:
a) 2x-(1-4x)=2+(8x-5)
b) 4-2(5-x)=x-4(x-1)
c) 7-(3x+4)=(x=1)-(2x+4)
d) x+3-(4-x)=3x-(2x-3)


3.Rozwiąż równania:
a) 2x-7-[3-2x-2(1-2x)]=x-11
b)10-[2(1-x)-3(2x+5)]=2(x+5)+1
c) 8-3x-2[4-(x+5)]=3(x+1)-1
d) 1-2x-3[2x-(-5+x)]=x+4

1

Odpowiedzi

2010-03-19T20:16:21+01:00
1.Rozwiąż równania:
a)
3(3-x)+2x=8-2(x-1)
9-3x+2x=8-2x+2
-3x+2x+2x=8+2-9
x=1

b)
4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
4x-3x-2x=4-4-5+6
-x=1
x=-1

c)
4-5(3-x)=-x-(3-2x)
4-15+5x=-x-3+2x
5x+x-2x=-3-4+15
4x=8
x=2

d)
x-(7+2x)=2(x-1)+1
x-7-2x=2x-2+1
x-2x-2x=-2+1+7
-3x=6
x=-2

2.Rozwiąż równania:
a)
2x-(1-4x)=2+(8x-5)
2x-1+4x=2+8x-5
2x+4x-8x=2-5+1
-2x=-2
x=1

b)
4-2(5-x)=x-4(x-1)
4-10+2x=x-4x+4
2x-x+4x=4-4+10
5x=10
x=2

c)
7-(3x+4)=(x+1)-(2x+4)
7-3x-4=x+1-2x-4
-3x-x+2x=1-4-7+4
-2x=-6
x=3

d)
x+3-(4-x)=3x-(2x-3)
x+3-4+x=3x-2x+3
x+x-3x+2x=3-3+4
x=4


3.Rozwiąż równania:
a)
2x-7-[3-2x-2(1-2x)]=x-11
2x-7-[3-2x-2+4x]=x-11
2x-7-3+2x+2-4x=x-11
2x+2x-4x-x=-11+7+3-2
-x=-3
x=3

b)
10-[2(1-x)-3(2x+5)]=2(x+5)+1
10-[2-2x-6x-15]=2x+10+1
10-2+2x+6x+15=2x+10+1
2x+6x-2x=10+1-10+2-15
6x=-12
x=-2

c)
8-3x-2[4-(x+5)]=3(x+1)-1
8-3x-2[4-x-5]=3x+3-1
8-3x-8+2x+10=3x+3-1
-3x+2x-3x=3-1-8+8-10
-4x=-8
x=2

d)
1-2x-3[2x-(-5+x)]=x+4
1-2x-3[2x+5-x]=x+4
1-2x-6x-15+3x=x+4
-2x-6x+3x-x=4-1+15
-6x=18
x=-3
12 5 12